2019
DOI: 10.1177/0269215519842254
|View full text |Cite
|
Sign up to set email alerts
|

The clinical- and cost-effectiveness of functional electrical stimulation and ankle-foot orthoses for foot drop in Multiple Sclerosis: a multicentre randomized trial

Abstract: Objective: To compare the clinical- and cost-effectiveness of ankle-foot orthoses (AFOs) and functional electrical stimulation (FES) over 12 months in people with Multiple Sclerosis with foot drop. Design: Multicentre, powered, non-blinded, randomized trial. Setting: Seven Multiple Sclerosis outpatient centres across Scotland. Subjects: Eighty-five treatment-naïve people with Multiple Sclerosis with persistent (>three months) foot drop. Interventions: Participants randomized to receive a custom-made, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 37 publications
(51 reference statements)
0
43
0
Order By: Relevance
“… 5 Remelius et al 2012, USA [ 73 ] To investigate (1) whether previously observed changes in gait parameters in individuals with multiple sclerosis (MS) are the result of slower preferred walking speeds or reflect adaptations independent of gait speed; and (2) the changes in spatiotemporal features of the unstable swing phase of gait in people with MS. Cross-sectional study; n = 19 PwMS, mean age 51.3 Gait analysis Longer dual support time is part of a gait strategy in MS that is apparent even when controlling for the confounding effect of slower preferred speed. 4 Renfrew et al 2019 UK [ 74 ] To compare the clinical- and cost-effectiveness of ankle-foot orthoses (AFOs) and functional electrical stimulation (FES) over 12 months in people with Multiple Sclerosis with foot drop. Multicentre, powered, non-blinded, randomized trial; n = 85 PwMS divided into n = 43 AFO group, n = 42 FES device group Walking speed Both devices demonstrated improvements in walking speed at 12 months, although there were no significant differences in their effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Remelius et al 2012, USA [ 73 ] To investigate (1) whether previously observed changes in gait parameters in individuals with multiple sclerosis (MS) are the result of slower preferred walking speeds or reflect adaptations independent of gait speed; and (2) the changes in spatiotemporal features of the unstable swing phase of gait in people with MS. Cross-sectional study; n = 19 PwMS, mean age 51.3 Gait analysis Longer dual support time is part of a gait strategy in MS that is apparent even when controlling for the confounding effect of slower preferred speed. 4 Renfrew et al 2019 UK [ 74 ] To compare the clinical- and cost-effectiveness of ankle-foot orthoses (AFOs) and functional electrical stimulation (FES) over 12 months in people with Multiple Sclerosis with foot drop. Multicentre, powered, non-blinded, randomized trial; n = 85 PwMS divided into n = 43 AFO group, n = 42 FES device group Walking speed Both devices demonstrated improvements in walking speed at 12 months, although there were no significant differences in their effects.…”
Section: Resultsmentioning
confidence: 99%
“…Some interventions aimed to support lower extremity health in patients with MS. Most of the intervention studies ( n = 12) were focused on improving lower extremity muscle strength, [ 52 , 53 , 64 , 83 ] walking, [ 53 , 55 , 65 , 69 , 70 , 74 , 76 , 77 , 83 ] balance, [ 51 , 52 ] mobility [ 52 ] or kinematics in the lower extremities [ 76 ]. The interventions varied from various physical training methods to foot orthoses.…”
Section: Resultsmentioning
confidence: 99%
“…Such evidence is required not only in the context of clinical trials but also in real-life clinical practice. 16,17 Economic analysis of individual interventions such as home-exercise programmes, functional electrical stimulation, and schemes to keep people in work have been reported, [18][19][20][21][22][23][24] but there is no published evaluation of the cost-efficiency of holistic multidisciplinary specialist rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Walking speed is increased similar to use of an ankle foot orthosis; however, little is known about the cost-effectiveness of functional electrical stimulation. 15…”
Section: Introductionmentioning
confidence: 99%
“…Walking speed is increased similar to use of an ankle foot orthosis; however, little is known about the cost-effectiveness of functional electrical stimulation. [1][2][3][4][5] Increase in walking speed is most often reported to reflect clinical efficacy and in fact walking speed has previously been used as a surrogate marker of quality of life in determining cost-effectiveness of functional electrical stimulation; 6 however, other effects such as increase in confidence, reduced falls or less effort of walking may all contribute to increased participation and are equally important. 7 Investigators have looked at the effect of functional electrical stimulation on the Psychosocial Impact of Assistive Device Scale, a measure of the impact of an assisted device on the user's self-esteem, adaptability (impact on participation) and competence (aspects of walking).…”
Section: Introductionmentioning
confidence: 99%